PENGARUH METODE BERMAIN FLASHCARD TERHADAP KEMAMPUAN KOGNITIF PADA ANAK DALAM PENCEGAHAN COVID-19 - Faqih, Moh Ubaidillah; Nurus Safa'ah; Suhartono (Jurnal Penelitian Sekolah Tinggi Ilmu Kesehatan Nahdlatul Ulama Tuban, 2021)
School children are the main targets for various delays in development, one of which has occurred in this pandemic era is delays in cognitive abilities in preventing COVID-19. Cognitive abilities in children in preventing COVID-19 can be improved by playing Flashcards. The purpose of this study was to determine the effect of the Flash Card playing method on cognitive abilities in children in preventing COVID-19 at MI Miftahul Huda Tegalrejo. The design used in this study was pre-experimental using a one-group pre-post-test research design with a simple random sampling technique. The sample in this study were children in grades 1A and 1B, totaling 25 children with a total population of 27 children. The results obtained in this study that before being given the Flash Card playing method, most of the children had undeveloped cognitive abilities, namely 16 (64%) children, while after being given treatment most of the children had cognitive abilities that developed as expected, namely 16 (64%) children. The statistical test used is the Wilcoxon test. Based on the results of statistical tests using the Wilcoxon test, the Asym value was obtained. Sig  (2-tailed) =  0.000 (<0.05), then  H1  is accepted so that the Flash Card playing method affects cognitive abilities in children in preventing COVID-19. These results are expected to be applied at MI Miftahul Huda Tegalrejo to improve cognitive abilities in preventing COVID-19.